2020
DOI: 10.47363/jccsr/2020(2)134
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Hygiene Management- A Study among Adolescent Girls in Five Schools in Bo District, Sierra Leone

Abstract: Menstruation can place significant impacts on girl’s health and education if they are not properly informed about effective menstrual hygiene management. The present study was undertaken to assess the knowledge and practices of menstrual hygiene among adolescent girls in five schools in Bo district, Sierra Leone and to assess the restrictions practiced by them during menstruation. A cross sectional study design was carried out among 103 in November 2019. A self-administered structured questionnaire at schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, it has a secondary or indirect impact on the ability of females to manage their menstrual hygiene; even in the best of times, females fail to manage their menstrual hygiene properly. In this emergency, this condition has worsened as lockdown has badly impacted the manufacture, supply, and availability of products [11]. Reports revealed that around 67% of normal manufacturing operations and distribution have paused, and 22% of organizations reported no access to menstrual hygiene products, which is most affected in rural regions.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
“…However, it has a secondary or indirect impact on the ability of females to manage their menstrual hygiene; even in the best of times, females fail to manage their menstrual hygiene properly. In this emergency, this condition has worsened as lockdown has badly impacted the manufacture, supply, and availability of products [11]. Reports revealed that around 67% of normal manufacturing operations and distribution have paused, and 22% of organizations reported no access to menstrual hygiene products, which is most affected in rural regions.…”
Section: Impact Of Covid-19mentioning
confidence: 99%